Comparison of the inoculum effect of in vitro antibacterial activity of Imipenem/relebactam and Ceftazidime/avibactam against ESBL-, KPC- and AmpC-producing Escherichia coli and Klebsiella pneumoniae - Xueting Wang; Luying Xiong; Yuan Wang; Kai Yang; Tingting Xiao; Xiaohui Chi; Tao Chen; Yanzi Zhou; Ping Lu; Dilimulati Dilinuer; Pin Shen; Yunbo Chen; et al. (BMC, 2023)
Abstract Objective To evaluate effect of inoculum size of extended-spectrum β-Lactamase (ESBL)-producing-, AmpC-producing-, and KPC-producing Escherichia coli and Klebsiella pneumoniae on the in vitro antibacterial effects of imipenem/relebactam (IMR) and ceftazidime/avibactam (CZA). Methods We compared the impact of inoculum size on IMR and CZA of sixteen clinical isolates and three standard isolates through antimicrobial susceptibility tests, time-kill assays and in vitro PK/PD studies. Results When inoculum size increased from 105 to 107 CFU/mL, an inoculum effect was observed for 26.3% (5/19) and 52.6% (10/19) of IMR and CZA, respectively; time-kill assays revealed that the concentration of CZA increased from ≥ 4 × MIC to 16 × MIC to reach 99.9% killing rate against K. pneumoniae ATCC-BAA 1705 (KPC-2-, OXA-9- and SHV-182-producing) and 60,700 (SHV-27- and DHA-1-producing). While for IMR, a concentration from 1 × MIC to 4 × MIC killed 99.9% of the four strains. When the inoculum size increased to 109 CFU/mL, neither IMR nor CZA showed a detectable antibacterial effect, even at a high concentration. An in vitro PK/PD study revealed a clear bactericidal effect when IMR administered as 1.25 g q6h when inoculum size increased. Conclusion An inoculum effect on CZA was observed more frequent than that on IMR. Among the β-lactamase-producing strains, the inoculum effect was most common for SHV-producing and KPC-producing strains.